Hubungan Anemia Defisiensi Besi pada Ibu Hamil dengan Kejadian Abortus di Ruangan Kasuari Rumah Sakit Umum Anutapura Palu - Lisda Widianti (Jurnal Kesehatan, 2017)
Factors that can lead to abortion were the factor of fetal, maternal factor, father factor, factors of infection and nutritional factors. Maternal factor that commonly happen were iron deficiency anemia. This study was to determine a relation of iron deficiency anemia in pregnant women with abortion. This study was conducted in Kasuari Anutapura Public Hospital, Palu, Central Sulawesi. This study was cross sectional design. Samples were taken with consecutive sampling technique, as many as 46 people. Data were analyzed with chi square test with p-value of 0,05. Results showed that there was a relationship between iron deficiency anemia in pregnant women with abortion, in Kasuari Anutapura Public Hospital, Palu.